СOMPARATIVE ANALYSIS OF VOLATILITY OF CRYPTOCURRENCIES AND FIAT MONEY - Beketnova, Yulia; Krylov, Grigory; Polyakov, Leonid; Denisenko, Andrey; Sat, Diana (Revista Inclusiones, 2020)
The object of the research is the leading national fiat currencies and transnational anonymous analogues of the currency. They have received the slang name of cryptocurrencies. The subject of the study is volatility. It is the most important financial indicator in the management of financial flows, as a measure of risk of using a financial instrument at a specified time interval. The subject of the research requires consideration of digital goods of limited emission, which are the product of energy conversion into information in the form of a program code on a tangible medium. The limited amount of the emission for these goods without the syndrome of “printing press” has served as a basis for the name “cryptocurrency” and “digital gold”. The issue of cryptocurrency is a reward in the competitive procedure of checking transactions in peer-to-peer networks that implement the technology of distributed registries, and it is essentially a by-product of their functioning. The significant feature of such a product is anonymity and cross-border. They give rise to fundamental legal issues. Cryptocurrency obtaining technology is available to general public and has become an innovative phenomenon. The latest financial phenomena need to be investigated, so it is necessary to conduct a multilateral scientific analysis, identification and comparison of cryptocurrency with the fiat currency. The article compares the volatility of different currencies such as fiat (US dollar, euro, Chinese yuan and Japanese yen) and the most popular cryptocurrencies (Bicoin, Litecoin, Ethereum and Monero) at the present time. The aim of the study is to obtain new estimates of cryptocurrency based on the use of tools such as GARCH model, simple historical volatility (SHV) and developed by the authoring tool, which is based on the Chaikin method.